Tradisi Mahar Berupa Emas Pada Perkawinan Masyarakat Kecamatan Tanjung Senang Perspektif Hukum Islam Dan Hukum Posistif - Jayusman, Jayusman; Jayusman; Shafra; Miti Yarmunida; Nurfatati (Universitas Islam Negeri Raden Fatah Palembang, 2024)
Dowry is a condition of marriage. However, the shape and size are not specified. Anything of value can be used as a dowry. The tradition of the people of Tanjung Senang sub-district is that the dowry is in the form of gold. The problem of this research is: what is the perspective of Islamic law on the practice of dowry in the form of gold in the Tanjung Senang sub-district community? After collecting data in the form of interviews and analyzing it, this research concludes that: The tradition of dowry in the form of gold is inherent and brings benefits to the people of Tanjung Senang District, and is in line with Islamic law and Positive Law in Indonesia. The dowry value is related to the education, profession, and social status of the future wife and husband, and the family discussions between both parties. There is a wedding dowry in the form of gold alone or added with other items. This tradition is in line with and accommodated by Islamic law and positive law in Indonesia.